THE WIEKTS - Eugenia Lupita; Budi Darma (Kata Kita: Journal of Language, Literature, and Teaching, 2014)
In this project, I would like to convey the reality of a patriarchal society through fiction and more specifically, fantasy. This project focuses on the lives of the four major characters representing a patriarchal family. It also focuses on the struggles that each of the characters have between following their own passion and the social expectations. The two themes used in this project are individual against society and male gender roles with the hegemonized patriarchal value as the basis. These values became the burden that men have to take in order to be accepted by the society. To portray this reality through fiction, I am using the realistic fantasy, a sub-genre of fantasy, as the genre of the four stories.